2002
DOI: 10.2337/diacare.25.10.1709
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Soy Phytoestrogen Intake in Postmenopausal Women With Type 2 Diabetes

Abstract: OBJECTIVE -Phytoestrogen consumption has been shown to reduce risk factors for cardiovascular disease. Type 2 diabetes confers an adverse cardiovascular risk profile particularly in women after menopause. The aim of this study was to determine whether a dietary supplement with soy protein and isoflavones affected insulin resistance, glycemic control, and cardiovascular risk markers in postmenopausal women with type 2 diabetes. RESEARCH DESIGN AND METHODS-A total of 32 postmenopausal women with diet-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
204
5
15

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 301 publications
(241 citation statements)
references
References 34 publications
15
204
5
15
Order By: Relevance
“…As suggested in previous studies, some of the soy's effects may be influenced by menopausal status and obesity (Jayagopal et al, 2002). Our study indicated that the potential benefit from consuming tofu and other soy products was primarily confined to postmenopausal women with a low BMI.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…As suggested in previous studies, some of the soy's effects may be influenced by menopausal status and obesity (Jayagopal et al, 2002). Our study indicated that the potential benefit from consuming tofu and other soy products was primarily confined to postmenopausal women with a low BMI.…”
Section: Discussionsupporting
confidence: 74%
“…Animal studies have demonstrated that soy protein and soy isoflavones improve glycemic control, lower insulin requirement, and increase insulin sensitivity (Vahouny et al, 1985;Iritani et al, 1997;Wagner et al, 1997;Lavigne et al, 2000). Similar benefits have also been documented in several intervention studies with soy supplements (soy protein, soy fiber, and soy isoflavones), but results have been inconsistent (Mahalko et al, 1984;Lo et al, 1986;Hermansen et al, 2001;Jayagopal et al, 2002). One cross-sectional study has examined the effect of usual dietary intake of isoflavones on glucose metabolism and observed an inverse association with insulin level (Goodman-Gruen & Kritz-Silverstein, 2001).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our subjects received Ͼ150 times this amount, yet no significant changes were observed over a 3-month period. The dose of isoflavones given was the same we used with 30 g soy protein, which reduced these cardiovascular and glycemic parameters within the same time frame (11). In addition, supplementation with isoflavones alone (40 -150 mg/day) in subjects without diabetes showed that there was no change in lipid profile in peri/postmenopausal women, both healthy and mildly hypercholesterolemic (18,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the addition of oral supplements, such as soy products, as part of a healthy diet has attracted recent interest because of their beneficial effects on lipid profiles (5-10). However, scant information is available on the effects of soy in individuals with type 2 diabetes (11)(12)(13), who are at higher risk due to hyperlipidemia, lower HDL levels, and abnormalities in LDL/lipoprotein composition (14). It also remains unclear whether a beneficial effect can be attributed to the soy protein or isoflavones.…”
mentioning
confidence: 99%